Novel Prognostic Biomarkers in Metastatic and Locally Advanced Colorectal Cancer: Micronuclei Frequency and Telomerase Activity in Peripheral Blood Lymphocytes - Nikolouzakis, Taxiarchis Konstantinos; Vakonaki, Elena; Stivaktakis, Polychronis D.; Alegakis, Athanasios; Berdiaki, Aikaterini; Razos, Nikolaos; Souglakos, John; Tsatsakis, Aristidis; Tsiaoussis, John (Frontiers in Oncology, 2021)
Purpose: Due to the current practice on colorectal cancer (CRC) management, chemoresistance is most often recognized at the end of the treatment. Therefore, effective and easy-to-use prognostic biomarkers are need. Experimental design: We evaluated the prognostic significance of two novel CRC biomarkers: a) micronuclei frequency (MNf) in 55 metastatic CRC (mCRC) and 21 locally advanced rectal cancer (laRC) patients using cytokinesis block micronucleus assay (CBMN assay) and b) telomerase activity (TA) in 23 mCRC and 5 laRC patients using TRAP-ELISA. Both biomarkers were evaluated in peripheral blood lymphocytes (PBLs) before, at the middle and at the end of the therapy (approximately 0, 3 and 6 months) for mCRC patients and before, at the end of the therapy and after surgery for laRC patients. Results: Overall, MNf demonstrated significant prognostic value since a decrease of MNf less than 29% between middle and initial MNf measurements can discriminate between progressive and stable/responsive disease with sensitivity 36% and specificity 87.0% while being able to identify responsive disease with sensitivity of 72.7% and specificity 59.3%. On the other hand, TA presented a significant trend of increase (p=0.07) in patients with progressive disease at the middle measurement. Conclusions: The findings of this study suggest that the MN frequency may serve as a promising prognostic biomarker for the monitoring of the treatment response of patients with CRC while TA should be evaluated in a larger group of patients to further validate its significance.